Prior knowledge-based precise diagnosis of blend sign from head computed tomography - Wang, Chen; Yu, Jiefu; Zhong, Jiang; Han, Shuai; Qi, Yafei; Fang, Bin; Li, Xue (Frontiers in Neuroscience, 2023)
Automated diagnosis of intracranial hemorrhage on head computed tomography (CT) plays a decisive role in clinical management. This paper presents a prior knowledge-based precise diagnosis of blend sign network from head CT scans. We employ the object detection task as an auxiliary task in addition to the classification task, which could incorporate the hemorrhage location as prior knowledge into the detection framework. The auxiliary task could help the model pay more attention to the regions of hemorrhage, which is beneficial for distinguishing the blend sign. Furthermore, we propose a self-knowledge distillation strategy to deal with inaccuracy annotations. In the experiment, we retrospectively collected 1749 anonymous non-contrast head CT scans from the First Affiliated Hospital of China Medical University. The dataset contains three categories: no intracranial hemorrhage (non-ICH), normal intracranial hemorrhage (normal ICH), and blend sign. The experimental results demonstrate that our method performs better than other methods. In addition, our method has the potential to assist less-experienced head CT interpreters, reduce radiologists’ workload, and improve efficiency in natural clinical settings.